Mobile Hadis Bukhari application: searching similar documents / Afiqah Zafirah Ahmad - Ahmad, Afiqah Zafirah (2010)
The application is developed to create a Mobile Hadis Bukhari by searching similar document. This courseware is developed for people who have mobile phone and for the easiness to people who want to search Hadis Bukhari instantly. The application will only specific on Hadis Bukahri from Jilid 100-180 only. Through the development of the application will help people to satisfy their needs. The study focuses on how to develop the application so that it can be used in mobile and how accurate the application is compare to web-based application.